Polysaccharide peptides from Coriolus versicolor: A multi-targeted approach for the protection or prevention of alcoholic liver disease. (January 2018) - Ren, Yilin; Geng, Yan; Chen, Hedi; Lu, Zhen-Ming; Shi, Jin-Song; Xu, Zhenghong
Highlights: Investigated the preventive effect of PSP on alcohol-induced liver injury in mice. PSP alleviates alcoholic fatty liver via the AMPK pathway. PSP regulates ethanol-induced endotoxin-mediated inflammation. PSP has potential as a dietary supplement or prescription for ALD. Abstract: Alcoholic liver disease (ALD) is a major cause of liver-related morbidity and mortality worldwide. In this paper, we investigated the preventive effect of polysaccharide peptide (PSP), isolated from JNPF-CV05 strain of Coriolus versicolor, on alcohol-induced liver injury in mice. Our data demonstrated that PSP supplementation attenuated ethanol-induced aspartate transaminase (ALT), aspartate transaminase (AST), and microscale malondialdehyde (MDA). Pre-treatment with PSP also significantly decreased ethanol-induced plasma levels of total cholesterol (TC), triacylglycerol (TG), and endotoxin concentration. Mechanistically, PSP treatment upregulated ethanol stimulated the hepatic expression of AMP-activated protein kinase (AMPK), acetyl-CoA carboxylase (ACC) and peroxisome proliferator–activated receptor α (PPARα) to inhibit hepatic lipid accumulation. In addition, PSP markedly reduced ethanol stimulated inflammation via inhibiting Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4) mediated nuclear transcription factor- kappa B (NF-κB) signaling pathway. In conclusion, PSP is effective in ameliorating ethanol-induced hepatic steatosis and injury through reducing lipid accumulation during the development of fatty liver and alleviating endotoxin-mediated inflammation. Our findings strengthen that PSP has potential as a dietary supplement or prescription for ALD.